(untitled) (LACCEI, 2024)
As a result of the COVID-19 pandemic, many bicycle lanes have been built in the city of Lima, as an efficient and eco-friendly transportation system that, among its main objectives, is to encourage the use of bicycles as a means of transportation and ultimately reduce environmental pollution in the city of Lima. However, due to pressures on design times and poor planning during its construction, poorly located bicycle lanes have been generated that are not used by the expected number of users and, in the worst cases, have been built over vehicle lanes. This reduces the number of vehicles that can circulate along the stretches in question and increases the amount of emissions due to vehicular congestion. The present study aims to evaluate the advantages or disadvantages of bicycle lanes in a specific area of the city of Lima, developing a discrete simulation model that allows comparing vehicular congestion in different scenarios, with the subsequent purpose of optimally designing a network of bicycle lanes in that area.